Thermal design analysis of a liquid hydrogen vessel - Kim, SY; Kang, BH (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Thermal analysis has been performed to design a high-performance liquid hydrogen (LH2) vessel. Analysis includes the combined insulation of multi-layer insulation (MLI) and vapor-cooled radiation shield (VCS) under high vacuum. Three types of combined insulation schemes are considered in this study; fully-filled MLI and serial-type double vapor-cooled radiation shield (DVCS); fully-filled MLI and parallel-type DVCS; partially-filled MLI and single vapor-cooled radiation shield (SVCS). Thermal analysis for a vapor-cooled heat station to reduce solid conduction heat in-leak through a filling tube is also made. The results indicate that the serial-type DVCS vessel shows better performance than parallel-type DVCS vessel. The combined insulation of SVCS and partially-filled MLI shows a similar performance compared to that of DVCS and fully-filled MLI. The vapor-cooled heat stations can enhance substantially the performance of the vessel for cryogenic fluids with high C-p/h(fg), where C-p the specific heat and h(fg) the latent heat of vaporization, such as LH2 and liquid helium (LHe). (C) 1999 International Association for Hydrogen Energy. Published by Elsevier Science Ltd. All rights reserved.